2016
DOI: 10.1200/jco.2016.34.4_suppl.403
|View full text |Cite
|
Sign up to set email alerts
|

Radiological markers of treatment responsiveness in patients (pts) with metastatic pancreatic ductal adenocarcinomas (mPDAC) receiving systemic chemotherapy.

Abstract: 403 Background: mPDAC is a deadly disease with dismal survival. Newer systemic therapies including gemcitabine/nab-paclitaxel (GA) and FOLFIRINOX (FF) have resulted in modest increases in median overall survival(mOS). Currently, no good predictors exist to prioritize the use of one regimen over the other. We investigated imaging patterns in patients receiving these two regimens. Methods: A single institution retrospective analysis of pts with mPDAC receiving either GA or FF as the front-line therapy between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In nine studies that reported data separately for the two regimens, 9–76% of patients treated with nab-P/G as first-line therapy received second-line therapy versus 9–94% of those treated with FOLFIRINOX as first-line therapy. 11,17,19,26,29,39,40,42,46 Overall, one study reported that 44% of patients received second-line chemotherapy. 33 Only two of these studies reported OS data in patients receiving second-line therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In nine studies that reported data separately for the two regimens, 9–76% of patients treated with nab-P/G as first-line therapy received second-line therapy versus 9–94% of those treated with FOLFIRINOX as first-line therapy. 11,17,19,26,29,39,40,42,46 Overall, one study reported that 44% of patients received second-line chemotherapy. 33 Only two of these studies reported OS data in patients receiving second-line therapy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, healthier/younger patients treated more frequently with FOLFIRINOX versus nab-P/G may have confounded the results in some studies. 17,23,26,27,31,37,40 Finally, although data regarding cost have been presented, few studies report this type of information, and it is typically difficult to standardize or quantify.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical trials comparing nab -P/Gem with FOLFIRINOX for the treatment of PC have not yet reported results, retrospective analyses have explored these standard-of-care regimens with one another and/or Gem for the treatment of MPC. 11 , 12 , 26 29 One study reported a median OS of 10.2 months with nab -P/Gem (n=189) versus 11.2 months with FOLFIRINOX (n=666) and 7 months for Gem combined with other chemotherapies (n=1,567). 11 Similar results were reported from another retrospective analysis: median OS of 11.6 months with nab -P/Gem (n=41) versus 13 months with FOLFIRINOX (n=101) and 7.5–9.1 months for Gem plus other chemotherapies (n=277).…”
Section: Resultsmentioning
confidence: 99%